The possibility of a significant increase in the level of motor activity in students with the use of the potential of computer technology - A.Yu. Osipov; M. D. Kudryavtsev; Yu.A. Kopylov; V.A. Kuzmin; E.V. Panov; I. E. Kramida (Physical Education of Students)
Purpose : a significant increase in the level of everyday motor activity of students. It is intended to use the collection and exchange of data on the daily mobility of students in popular online networks and mobile applications. Identify the prospects for using social networks and mobile applications in the control and management of the body weight of students. Material : The study involved students (n = 30, age 19-20 years). Admission to the group occurred by sending out invitations to social networks. The main criteria for selecting female students are the same age and absence of diseases. Also taken into account the indicators of the body weight of female students. It was used the following methods for assessing the level of physical condition of female students: control over the body weight (weighing), time parameters of recovery of the body after performing a test load (sample with 30 sit-ups). To evaluate the results of the studies, the Wilcoxon signed-rank test was used. Results : multidirectional dynamics of changes in body weight data was detected among female students. In the control group, there was a slight increase in body weight. In the experimental group, a significant decrease in body weight was found. The recovery time significantly decreased by an average of 7±1 seconds (experimental group) and by 2±1 seconds (control group). The volume of daily motor activity of female students of both groups significantly increased. The students of the experimental group have higher rates of motor activity. Conclusions : the possibilities of using social networks and mobile applications are shown to increase the daily motor activity of students and the possibility of correcting body weight.